The impact of early postnatal environmental enrichment on maternal care and offspring behaviour following weaning - Ki, Angel Li; Torp Lund, Emilie; Voigt, Jörg-Peter (Elsevier, 2016)
The early postnatal period is a sensitive period in rodents as behavioural systems are developing and maturing during this time. However, relatively little information is available about the impact of environmental enrichment on offspring behaviour if enrichment is implemented only during this period. Here, environmental enrichment was provided from postnatal day 1 until weaning. On post-natal day 9, maternal behaviour and nonmaternal behaviour of the dam was observed. Nursing time in the enriched group was reduced but dams showed more non-maternal appetitive behaviours. Offspring were exposed to either the open field or the elevated plus maze (EPM) after weaning. In the open field, rats from the enriched group approached the more aversive inner zone of the open field later than control rats. Offspring from the enriched group made fewer entries into the inner zone and spent less time in this part of the arena. Enrichment had no impact on behaviour in the EPM. The present study provides evidence that postnatal enrichment can interfere with maternal behaviour in rats and can possibly lead to increased anxiety in the offspring. The findings suggest that enrichment procedures can have potentially unintended effects, interfering with the development of emotional behaviours in rats.